ANALISIS KETERAMPILAN KONEKSI MATEMATIS PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA ALJABAR - Fauziah Indria Pramesti; Defahayu As Syaura Al Hawari; Alma Aulia Hanifah; Mulin Nu’man (Program Studi Pendidikan Matematika Universitas Kuningan, 2025)
Despite the vital role mathematical connection skills play in linking mathematical concepts to other disciplines and everyday life, previous research indicates that student achievement in this area remains suboptimal, and the specific indicators of these skills have not yet been comprehensively examined. This study aimed to describe students' skills in connecting mathematical concepts while solving algebraic word problems. A qualitative, descriptive approach was employed. The study was conducted from October to November of the 2023/2024 academic year at SMP Negeri 15 Yogyakarta, involving students from class VII H. Data were collected through tests and documentation, with the test serving as the instrument to measure students' ability to establish mathematical connections. Among the 32 participating students, the results indicated that 20 fell into the high-ability category, 2 into the medium category, and 10 into the low category. Overall, the findings reveal that the majority of class VII-H students demonstrated a high level of mathematical connection skills. The researcher recommends that educators consistently encourage students to hone these skills, for instance, by providing regular practice exercises.